Demand For Fish Products In The Czech Republic - Milena BOTLÍKOVÁ (Communications of International Proceedings, 2021)
Tourism before the time of Covid-19 was manifested by dynamic growth. This increase is associated with globalization influences such as the ability to travel long distances, the desire for new experiences. Tourism has undergone many changes in recent times, from visual cognition to tourists also focusing on cognition through taste or olfactory perceptions. New trends thus add to the development of gastronomic tourism. Fish gastronomy is part of the cultural traditions in the Czech Republic, similar to Croatia, France or Bulgaria. This type of gastronomy is also an opportunity for the fishing company to diversify its business. A pandemic created by the transformation of the geographical regrouping of tourists, tourism will be more dependent on domestic tourism. The development of fish gastronomy in the near future will depend on the approach of Czech consumers to the fish product and on the ability of tourism entities to accept and support innovative trends. The article aims to identify the consumer behaviour of the Czech population in the market of fish products.
Keywords: Fish; Attitudes; Czech Republic; Gastronomy; Price.